Rapid recovery of body mass after surgical removal of adipose tissue in ground squirrels. - Dark, J (1984)
A substantial proportion of total adipose tissue mass was surgically removed from female ground squirrels during weight gain or weight loss phases of the circannual body weight cycle. Within 2 months of fat removal, squirrels had restored body mass to levels appropriate to the stage of the annual body weight cycle. These findings suggest that ground squirrels may use feedback from body lipids in controlling body weight.